Breeding Ecology of the Pied Avocet, Recurvirosrta avosetta (Charadriformes, Recurvirostidae), in Tiffech Lake (Souk Ahras, Northeastern Algeria) - Boukrouma, N. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2021)
In this study, the breeding ecology of the Pied Avocet (Recurvirostra avosetta) was studied during the 2017 breeding season in Tiffech Lake Wetland (868 m in elevation), Northeastern Algeria. Avocets arrived, at Tiffech Lake in early February and usually spent a few days in flocks before dispersing to set up territories. Egg-laying occurred from 11 April to 21 June, with two distinct peaks (last 15 days of April May) and incubation period was 27.0 days. The present study indicates the expanded, breeding season. Clutch and egg size of this high- elevation species was comparable to lowland counterparts. Hatching success was 85.77% and mean net productivity was 0.63 chicks per nest. Entire nest failure from human predation and sheep grazing was responsible for most egg losses.